Effects of Lifestyle Factors on Cognition in Minority Population of Older Adults: A Review - Eubank, Jacob M.; Oberlin, Douglas J.; Alto, Andrew; Sahyoun, Nadine R.; Asongwed, Elmira; Monroe-Lord, Lillie; Harrison, Elgloria A. (Frontiers in Nutrition, 2022)
The onset of dementia and Alzheimer’s disease (AD) is projected to expand over the next several decades in the United States as the population ages. However, the cognitive health burden is not equally distributed among the population, as Hispanics and African Americans are at higher risk of AD when compared with Non-Hispanic Whites. There is some evidence to indicate that cognitive decline may be associated with lifestyle factors and that interventions in these domains may prevent or delay this decline. These lifestyle factors include social engagement, physical activity, both aerobic and strength training, dietary intake, sleep and stress. This review summarizes, in general, what is known about the relationship between risk factors and cognition and, in particular what is known about this relationship in minority populations. The results show that the relationship between these risk factors and cognitive decline is stronger for some of the factors such as physical activity and dietary intake and weaker for the other factors depending on what is measured and in what populations. It does appear, however, that the studies in minority populations is limited and warrants more targeted research and interventions.